(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Denimba debatu kashaya is a renowned polyherbal formulation from the traditional Sri Lankan text Vatikaprakaranaya, where it is indicated as an Anupana kashaya (adjuvant decoction). In contemporary practice, it is widely used for managing infectious diseases. This study was designed to scientifically evaluate the in vitro antimicrobial potential of Denimba debatu kashaya, both with and without its traditional additives (Prativapa dravya), against common pathogens. The decoction was prepared according to classical guidelines and tested against Staphylococcus aureus (ATCC™ 25923), Escherichia coli (ATCC™ 25922), and a clinical isolate of Candida albicans using the agar well diffusion method. Augmentin (100µg/mL) and Itraconazole (100µg/mL) were used as positive controls. The results demonstrated that the Kashaya samples did not produce any measurable zone of inhibition (ZOI) against the tested microbes. However, a slight reduction in bacterial growth was observed near the sample wells. This suggests that the standard preparation may possess an intermediate or weak effect, or its therapeutic efficacy in traditional settings may be attributed to mechanisms other than direct antimicrobial action, such as immunomodulation. Further studies using higher concentrations are recommended to fully explore its antimicrobial properties.